Hydrogen Sulfide: An Emerging Regulator of Oxidative Stress and Cellular Homeostasis-A Comprehensive One-Year Review - Constantin Munteanu; Marius Alexandru Turnea; Mariana Rotariu (MDPI AG, 2023)
Hydrogen sulfide (H2S), traditionally recognized as a toxic gas, has emerged as a critical regulator in many biological processes, including oxidative stress and cellular homeostasis. This review presents an exhaustive overview of the current understanding of H2S and its multifaceted role in mammalian cellular functioning and oxidative stress management. We delve into the biological sources and function of H2S, mechanisms underlying oxidative stress and cellular homeostasis, and the intricate relationships between these processes. We explore evidence from recent experimental and clinical studies, unraveling the intricate biochemical and molecular mechanisms dictating H2S's roles in modulating oxidative stress responses and maintaining cellular homeostasis. The clinical implications and therapeutic potential of H2S in conditions characterized by oxidative stress dysregulation and disrupted homeostasis are discussed, highlighting the emerging significance of H2S in health and disease. Finally, this review underscores current challenges, controversies, and future directions in the field, emphasizing the need for further research to harness H2S's potential as a therapeutic agent for diseases associated with oxidative stress and homeostatic imbalance. Through this review, we aim to emphasize H2S's pivotal role in cellular function, encouraging further exploration into this burgeoning area of research.